2012
DOI: 10.1111/j.1742-7924.2012.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychosocial factors on metabolic syndrome in male and female blue‐collar workers

Abstract: Metabolic syndrome among blue-collar workers is closely related to psychosocial factors, such as job stress, social support, and risk perception, with the effect of job stress a point of difference between men and women. Occupational health nurses should be cognizant of the importance of assessing the effect of psychosocial factors on cardiovascular risk for blue-collar workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…100 In another study among Korean blue collar workers, who worked in jobs such as shipbuilding and manufacturing industry, effort-reward imbalance was associated with metabolic syndrome, characterized as the presence of all 5 components of the syndrome, in both men and women. 101 Although these studies are limited by their crosssectional design, several prospective studies have shown similar findings. In one study that followed up 290 police officers over a 5-year period, work stress, characterized as job strain or effort-reward imbalance, was associated with metabolic syndrome as well as hypertriglyceridemia, even after adjusting for numerous sociodemographic variables (namely, age, rank, education, geographic origin, marital status, housing, presence of offspring, smoking, and sleep habits).…”
Section: Potential Mechanisms For a Link Between Work Stress And Chdmentioning
confidence: 87%
See 1 more Smart Citation
“…100 In another study among Korean blue collar workers, who worked in jobs such as shipbuilding and manufacturing industry, effort-reward imbalance was associated with metabolic syndrome, characterized as the presence of all 5 components of the syndrome, in both men and women. 101 Although these studies are limited by their crosssectional design, several prospective studies have shown similar findings. In one study that followed up 290 police officers over a 5-year period, work stress, characterized as job strain or effort-reward imbalance, was associated with metabolic syndrome as well as hypertriglyceridemia, even after adjusting for numerous sociodemographic variables (namely, age, rank, education, geographic origin, marital status, housing, presence of offspring, smoking, and sleep habits).…”
Section: Potential Mechanisms For a Link Between Work Stress And Chdmentioning
confidence: 87%
“…This relationship was strongest among younger men . In another study among Korean blue collar workers, who worked in jobs such as shipbuilding and manufacturing industry, effort‐reward imbalance was associated with metabolic syndrome, characterized as the presence of all 5 components of the syndrome, in both men and women . Although these studies are limited by their cross‐sectional design, several prospective studies have shown similar findings.…”
Section: Potential Mechanisms For a Link Between Work Stress And Chdmentioning
confidence: 89%
“…Some researchers reported that MSx was more common in men. 10,22,23 However, some studies reported a higher prevalence in women. 24,25 We found that workers with MSx had a higher mean age than those without.…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient attention has been given to job factors such as job insecurity, physical exertion, chemical exposure and organizational hazards [6,7]. Studies all over the world have shown that depression, anxiety, and stress are a significant problem among blue collar workers [8][9][10][11]. More and more studies explore the relationship between psychosocial job factors and depression and stress [12][13][14].…”
Section: Research Instruments and Data Collectionmentioning
confidence: 99%